A Broader View for Plant EvoDevo: Novel Approaches for Diverse Model Systems - Jocelyn C. Hall (Frontiers Research Topics, 2017)
This collection attempts to integrate work pertaining to a fundamental question in plant evolution: What are the molecular underpinnings for the origin of different plant forms? Among the many facets this question touches are the transition to land, the emergence of vascular plants, the origin of the seed and the origin and diversification of floral form. We aim to bring to the forefront the most salient and original plant systems and approaches within an inclusive phylogenetic context that encompasses representatives of the major lineages of land plants.